NON-LINGUSITIC SEMIOTIC SYSTEM AND ITS ELEMENTS (Scientific journal of the Fergana State University, 2024)
Nonverbal means play an important role in the communication process, and choosing the necessary means during the conversation is important in increasing the effectiveness of the speech. In studying this type of communication, the importance of psychology, cultural studies, and sociology is significant. Because in the process of expressing an opinion about an event, people first of all think and approach based on their worldview, their position in society and the environment in which they live, which shows that the above disciplines are inextricably linked with linguistics. We know that linguistics consists of several branches, and each one deals with the study of the structure of speech in a specific process. The non-literary semiotic system is not far from it. In this article, we present our thoughts on the non-verbal system and its elements.